Post-combustion CO2 capture process: Equilibrium stage mathematical model of the chemical absorption of CO2 into monoethanolamine (MEA) aqueous solution - Mores, Patricia Liliana (2011)
This paper deals with the modeling and optimization of the chemical absorption process to CO2 removal using Monoethanolamine (MEA) aqueous solution. Precisely, an optimization mathematical model is proposed to determine the best operating conditions of the CO2 post-combustion process in order to maximize the CO2 removal efficiency. Certainly, two objective functions are considered for optimization. Temperature, composition and flow-rate profiles of the aqueous solution and gas streams along the absorber and regenerator as well as the reboiler and condenser duties are considered as optimization variables. The number of trays or height equivalent to a theoretical plate (HETP) on the absorber and regenerator columns as well as the CO2 composition in flue gas are treated as model parameters. Correlations used to compute physical-chemical properties of the aqueous amine solution are taken from different specialized literature and are valid for a wide range of operating conditions. For the modeling, both columns (absorber and regenerator) are divided into a number of segments assuming that liquid and gas phases are well mixed. GAMS (General Algebraic Modeling System) and CONOPT are used, respectively, to implement and to solve the resulting mathematical model. The robustness and computational performance of the proposed model and a detailed discussion of the optimization results will be presented through different case studies. Finally, the proposed model can not only be used as optimizer but also as a simulator by fixing the degree of freedom of the equation system.